The relationship between dimensions of intellectual capital and knowledge creation: Case Study of the headquarters of national gas corporation of Iran - Mehdi Sharafi; Yousof Mohammadi moghadam; Tavakol Sharafi (Management Science Letters, 2012)
Intellectual capital is the main property of any organization in knowledge-based economics. Knowledge is the fundamental principle of intellectual capital. Hence, it is the core of organizational capabilities. The aim of this study is to survey the relationship between dimensions of intellectual capital and knowledge creation in the headquarters of National Gas Corporation of Iran in the year 2010. The research method is descriptive – survey and follows practical objective. The research population consists of the formal staffs of the Corporation (managers, senior staff and other staff). We selected 261 people from the population randomly. We also used a reliable and valid questionnaire to gather data. We also used informative factor analysis to examine goodness of the model and we used SEM by Lisrel to confirm or reject the hypothesis in this study. The results show that all dimensions of intellectual capital have a significant impact on dimensions of knowledge creation, except for the effects of structural capital on knowledge combination as well as relational capital on knowledge internalization.